Analyzing the factors influencing entrepreneurial intentions among UiTM students - Mohammad Rasyidi, Nureen Maisarah; Abdul Wahab, Nur Amiera; Wan Baharuddin, Wan Nurul Nadhira; Mohamad, Nurul Syafika; Syed Zainal, Sharifah Nur Afiqah; Mat, Khalid Amin; Md. Shariff, Anita (Journal of Islamic, Social, Economics and Development, 2025)
This study aims to investigate the determinants of entrepreneurial intentions among students at Universiti Teknologi MARA (UiTM), focusing on the influence of attitude, perceived behavioural control (PBC), subjective norms, self-efficacy and emotional intelligence. A quantitative research design was employed, utilizing a structured questionnaire to collect data from 65 students. The data were analysed using SPSS, with reliability analysis, descriptive statistics, regression analysis and correlation analysis conducted to examine the relationships between the variables. The results indicate significant relationships between the independent variables and entrepreneurial intentions, with attitude and PBC being the strongest predictors. While self-efficacy and emotional intelligence were not statistically significant predictors, their moderate correlations with other variables suggest they may play indirect roles. The study concludes that creating a supportive environment that fosters positive attitudes and perceived control is crucial for developing future entrepreneurs.